Comparison of auction formats in Canadian government auctions - Olivier Armantier; Nourredine Lafhel (Bank of Canada, 2009)
Using a rich sample of Canadian government securities auctions, we estimate the structural parameters of a share-auction model accounting for asymmetries across bidders. We find little evidence of asymmetries between participants at Canadian government nominal bond auctions. A counter-factual analysis also suggests that given the assumptions underlying the model used, including that participation and quality of information are exogenous, the discriminatory format currently in place is superior to the uniform-price format in terms of the revenue generated by the Canadian government. Both auction formats, however, are found, under the same assumptions, to be dominated by the so-called Spanish auction” format.
Keywords: D44; G28; D63; 330; Debt management; Financial markets; Market structure and pricing; Debt Management; Öffentliche Anleihe; Auktion; Asymmetrische Information; Kanada